PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEOSCRIBE SPARKOL PADA MATERI KEKONGRUENAN DAN KESEBANGUNAN DI SMP PGRI 2 BOGOR - Ardistya Puspita Sari; Indra Martha Rusmana (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
This study aims to determine the feasibility of using learning media based on Videoscribe Sparkol on congruence and similarity material at SMP PGRI 2 Bogor. The method used in this study is the Research and Development method using ADDIE development procedures, namely (Analysis, Design, Development, Implementation, and Evaluation). The data collection method used an expert test validation questionnaire. The results of data analysis in the media validation process included media experts, namely 4.00 meaning "good", material experts, namely 4.00 intention "good", and development experts, namely 4.25 meaning "very good". It can be concluded that the average feasibility of learning media based on Sparkol videoscribe is feasible because the intermediate results are promising. This media development was carried out until expert testing and was not carried out in the field due to the Covid-19 pandemic in 2020